Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Batam - Dini Aulia; Mortisor Afrizal Purba (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Indonesia, a developing nation, has undertaken extensive development efforts across all sectors to foster a prosperous and thriving community. The tax sector is one of the primary sources of government funds. When we hear the term "tax," many of us automatically perceive it as a substantial extra responsibility during ongoing economic challenges that are progressively worsening. This study employs quantitative research methods to analyse numerical data and utilise statistical tests to examine the correlation, influence, or effect of independent variables on the dependent variable, specifically in connection to taxpayer compliance. The population for this study comprises all individuals who are enrolled as taxpayers at the SAMSAT Batam Joint Office in 2023, with a total of 959,218 taxpayers. The research findings indicate a significant result from the t-test, with a calculated value of 2.717 exceeding the critical value of 1.985 from the t-table. The significance value of the Motor Vehicle Taxpayer Compliance variable is 0.000, which is below the threshold of 0.05. The tax whitening programme variable has a considerable impact on the compliance of motor vehicle taxpayers. The t-test findings indicate a significant value of 5.088, which is greater than the t-table value of 1.985. The significance value of the Transfer of Name Duty Exemption is 2.717, which is greater than the threshold of 0.05. The t-test findings indicate a significant value of 3.072, which is greater than the t-table value of 1.985. The p-value for socialisation is 0.003, which is below than the significance level of 0.05. The t test findings indicate a significant level of 0.05 or 5%. The degrees of freedom (df1) for the numerator is 3 (number of variables minus 1), and the degrees of freedom (df2) for the denominator is 96 (total data number of variables minus df1 minus 1). The findings from the f-table are 2.70. The results indicate that there is a significant influence of the Tax Whitening Programme, Exemption from Transfer of Name Fees, and Socialisation on Motor Vehicle Taxpayer Compliance. This is evident from the f-count value of 29,673, which is greater than the f-table value of 2.70.